High Levels of Cartilage Oligomeric Matrix Protein in the Serum of Breast Cancer Patients Can Serve as an Independent Prognostic Marker - Papadakos, Konstantinos S.; Darlix, Amélie; Jacot, William; Blom, Anna M. (Frontiers in Oncology, 2019)
Background: Cartilage oligomeric matrix protein (COMP) is a pentameric cartilage protein also expressed in breast cancer tumors. A high expression of COMP evaluated by immunohistochemical staining is as an independent prognostic marker associated with poor patients' prognosis. Methods: Herein, levels of COMP were analyzed using an IVD approved ELISA in serum samples from 233 well-characterized breast cancer patients; 176 with metastatic breast cancer; and 57 in an early stage of the disease. Results: The metastatic patients had double the concentration of serum COMP compared with those with early breast cancer. High levels of COMP in sera of metastatic patients were associated with the histological subtype (p = 0.025) and estrogen receptor positivity (p = 0.019) at the time of breast cancer diagnosis. Further, correlation was observed between the serum levels of COMP and the presence of liver (p = 0.010) or bone (p = 0.010) metastases in this population. Most importantly, elevated serum levels of COMP appear to serve as an independent prognostic marker of survival as assessed by Cox proportional hazard regression analysis (p = 0.001) for the metastatic patients. Among metastatic patients treated with taxanes (Docetaxel-Paclitaxel) as part of their first metastatic line (n = 25), those with high levels of serum COMP detected in the metastatic stage of the disease had a shorter median survival (0.2 years) compared with those with low levels of serum COMP (1.1 years) (p = 0.001). Conclusions: Taken together, the serum levels of COMP are elevated in the metastatic patients and may be a potential novel biomarker for the evaluation of the prognosis in this population.